Digital health leadership: carving a new pathway - Shah, Sam (Future Healthc J, 2020)
Digital health is a novel and emerging field within healthcare, with a professional group that is evolving just as rapidly. In recent years, training opportunities within digital health have become more present in research, the NHS and the private sector. This article offers a personal reflection on a digital health leadership journey and makes the case for flexibility in training and career opportunities. If policy makers and senior leaders want to realise the outcomes from successive workforce reviews, such as The Topol Review, then there is a case for more inclusive digital leadership roles open to the widest range of suitably skilled professionals.